Cyclic Nanostructures of Tungsten Oxide WO3n (n=2–6) as NOx Gas Sensor: A Theoretical Study - Mohammad Izadyar; Azam Jamsaz (International Journal of Analytical Chemistry)
Today’s WO3-based gas sensors have received a lot of attention, because of important role as a sensitive layer for detection of the small quantities of  NOx. In this research, a theoretical study has been done on the sensing properties of different cyclic nanoclusters of WO3n  (n=2–6) for NOx  (x=1,2) gases. Based on the calculated adsorption energies by B3LYP and X3LYP functionals, from the different orientations of  NOx molecule on the tungsten oxide clusters, O–N⋯W was preferred. Different sizes of the mentioned clusters have been analyzed and W2O6 cluster was chosen as the best candidate for NOx detection from the energy viewpoint. Using the concepts of the chemical hardness and electronic charge transfer, some correlations between the energy of adsorption and interaction energy have been established. These analyses confirmed that the adsorption energy will be boosted with charge transfer enhancement. However, the chemical hardness relationship is reversed. Finally, obtained results from the natural bond orbital and electronic density of states analysis confirmed the electronic charge transfer from the adsorbates to WO3 clusters and Fermi level shifting after adsorption, respectively. The last parameter confirms that the cyclic clusters of tungsten oxide can be used as NOx gas sensors.